Andreas Vesalius of Brussels (1514–1564): his contribution to the field of functional neuroanatomy and the criticism to his predecessors. Issue 6 (1st November 2020) - Markatos, Konstantinos; Chytas, Dimitrios; Tsakotos, Georgios; Karamanou, Marianna; Piagkou, Maria; Mazarakis, Antonios; Johnson, Elizabeth
Abstract: Until the fifteenth century, the knowledge about anatomy and function of the nervous system had been significantly influenced by theological notions. Andreas Vesalius of Brussels (1514–1564), based on human cadavers' dissections, criticized his predecessors and contributed to the construction of the current knowledge about functional neuroanatomy. Although he did not avoid mistakes, he successfully demonstrated the high value of human cadavers' dissection in anatomical teaching.